Mary Tyler Moore : A Tribute - Sabiston, Elizabeth (Revue CMC Review, 2017)
In tribute to the late Mary Tyler Moore, the article examines her lasting influence on the depiction of women’s roles in the media, but also on the real aspirations of women in the workplace. It compares and contrasts the independent women depicted in “The Mary Tyler Moore Show” (Mary Richards) and the British “Avengers” (Emma Peel) to later constructions of women in the media.